Algae encapsulation into silica monoliths synthesized by high internal phase emulsions (HIPE) - López Pico, Nadia Priscila (2020)
Biotechnological applications of microalgae are widespread within different important research fields, from the oldest ones focused on human nutrition until the most novel ones as a renewable energy source; however, bioremediation of CO2 and biofuel production remains the most overwhelming application. These amazing organisms represent a substantial source of biomass for the production of high valuable metabolites as lipids and carbohydrates. Their metabolic activity is possible thanks to the photosynthesis where the chlorophyll molecule is directly involved in the beginning of a series of chemical reactions to obtain oxygen and sugars from CO2 and water in the presence of sun light. With the purpose of fixing CO2 through the efficient microalgae photosynthesis, this work proposes the algae encapsulation within a hierarchical porous silica monolith by using high internal phase emulsion (HIPE) as a new synthesis method to obtain bio-hybrid monoliths. To evaluate the viability and evolution of the immobilized microalgae within the monolithic structure of silica, this research was based on the fluorescent properties of their chlorophyll which was characterized by fluorescence spectroscopy and microscopy. Also, the characterization by diffuse reflectance spectroscopy in UV-Vis (DRS UV-Vis) was carried out to corroborate the qualitative analysis from fluorescence spectroscopy. The spectra from monoliths of successful encapsulation presented the relevant peaks from chlorophyll in both absorption and fluorescence modes. The novel and low cost technique developed in this work for Chlorella vulgaris immobilization achieved a log-term stability of at least 250 days. The photosynthetic activity was kept without constant feeding of microalgae. This bio-hybrid monolith could be applied in the future as an eco-friendly photo-bioreactor which captures CO2 and produces high-value raw materials as well as for water depollution.